Frontline Extension Professionals & COVID-19: Supporting Household Food Security & Building Resilience - Mary T. Rodriguez (Journal of International Agricultural and Extension Education, 2021)
The world was not prepared for the COVID-19 pandemic. It has tremendously impacted health and food systems around the world and the depth and breadth of its long-term effects are yet to be seen. The rates of those that will be in poverty and food insecure are significantly higher than the predictions pre-COVID. People are coping in any way that they can, at times in ways that will have lasting impacts on their households and communities. A community’s ability to absorb, adapt, and transform in the face of crisis can significantly impact how it is able to survive and thrive during those challenging times. A frontline extension professional can equitably build assets and thus capitals, ultimately increasing household and community resilience.
Keywords: COVID-19; food security; resilience; coping; Community CapitalsFramework